"Ramping up telemedicine in pediatric urology- Tips for using a new modality". Issue 3 (June 2020) - Finkelstein, Julia B.; Nelson, Caleb P.; Estrada, Carlos R.
Summary: The COVID pandemic has incited the rapid implementation of telehealth services. Through telemedicine, pediatric urologists can counsel children and their families about genitourinary tract conditions, while adhering to social distancing requirements and keeping families safe at home. With the accelerated use of telemedicine, it is crucial to maintain standards of providing high-quality and secure urologic care. Clinicians must practice effective virtual communication or 'webside' manner. While research may not be a priority, collecting data on telemedicine efforts will be critical in bringing about both payer-based and legislative reforms to encourage and enable wider telemedicine use in the post-COVID world.